Tense and aspect in Spanish and Zamboanga Chabacano verbs - Domingo, Pilar B. 1939- (1967)
This study identifies the problems that a Chabacano speaker may encounter in learning Spanish. It made use of a contrastive analysis based on Robert Lado's approach in contrasting languages. The researcher found out that there is a need for Chabacano learners of Spanish to identify regular and irregular verbs, root endings, concordance of person-number and their corresponding inflections, and tense and aspect patterns in Spanish.
Thesis (M.A.T. English)--University of the Philippines, Diliman.
Keywords: Spanish language -- Verb; Spanish language -- Dialects -- Philippines